Comparative Analysis of Classroom Management Practices and Teaching Methodologies across Educational Sectors in District D.I. Khan - Khan, Zafar; Mustafa, Javed; Rafiq, Ambreen (Journal of Development and Social Sciences, 2024)
This study aims to compare classroom management practices and teaching methodologies across government, semi-government, and private secondary schools in District D.I. Khan to identify sector-specific strengths and areas for improvement. A descriptive research design was employed, utilizing a Likert-scale questionnaire to collect data from 457 respondents. Statistical analyses, including mean comparisons and ANOVA, revealed that while classroom management practices showed no significant differences across sectors, teaching methodologies varied significantly. Government schools excelled in maintaining discipline and employing structured teaching practices such as lesson planning and the use of visual aids. Semi-government schools demonstrated strength in interactive and student-centered approaches, including the effective use of technology and maintaining clarity in communication. Private schools emphasized individualized attention and student engagement but showed inconsistencies in resource utilization and planning. These findings emphasize the need for sector-specific interventions to optimize teaching practices and improve educational outcomes, fostering equity and excellence across the educational landscape. It is recommended that interventions, such as technology integration, enhanced teacher training, equip teachers with necessary visual aids, and sectoral collaboration, are essential to optimize educational outcomes across all sectors.